Driven mechanisms of board commitment: A modified corporate CANE model. Issue 1 (February 2023) - Trinh, Vu Quang; Cao, Ngan Duong; Vo, Xuan Vinh
Abstract: The study employs a sample of US S&P 100 firms to explore the driving factors affecting the level of board commitment. We modified Clark's (1998) CANE model and developed a corporate CANE model that is applicable for board commitment. Supporting our model, we find that primary drivers of board commitment (through board personal agency) are non-financial factors including board independence, size, gender diversity, professional experience/skills, industrial and financial experiences, senior executives' compensation, and strictly board independence. These board compositions significantly enhance the level of board commitment, except the board size. On the other hand, whilst we find significant impact for the market-based factors, i.e. board commitment level tends to increase with market value (Tobin's Q), we find weak or no evidence on the effects of accounting-based factors. This suggests that the board task value is influenced by the actual perception of the market participants rather than 'documented' figures.